2019
DOI: 10.4102/sajce.v9i1.686
|View full text |Cite
|
Sign up to set email alerts
|

Home as a primary space: Exploring out-of-school literacy practices in early childhood education in a township in South Africa

Abstract: Post-1994, the democratic South African Government was not only concerned with the desegregation of the education system, but also with addressing poor literacy levels, specifically in primary schools (Bloch 2009). Of concern, South Africa still produces learners with very low literacy and numeracy levels (Fleisch 2008;Howie et al. 2012;Spaull 2013). Reports on educational achievement in South Africa demonstrate that far too many children in primary schools are performing poorly, often failing to acquire funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
0
8
1
Order By: Relevance
“…In addition, parents appreciated the quality of hygiene level and facilities in pre-school that was up to the mark and standard and can be further improved. These results contradicted the experiments of Sibanda and Kajee (2019) who considered children's out-of-school practices with the potential to sustain literacy development in school. Sibanda and Kajee concluded that children interact with multiple discourses during their everyday practices and play.…”
Section: Parents' Belief (10 Articles)contrasting
confidence: 79%
“…In addition, parents appreciated the quality of hygiene level and facilities in pre-school that was up to the mark and standard and can be further improved. These results contradicted the experiments of Sibanda and Kajee (2019) who considered children's out-of-school practices with the potential to sustain literacy development in school. Sibanda and Kajee concluded that children interact with multiple discourses during their everyday practices and play.…”
Section: Parents' Belief (10 Articles)contrasting
confidence: 79%
“…This is confirmed by the body of early literacy evidence detailing young children's emergent reading and writing prior to formal schooling (Whitmore et al 2004, Nutbrown 2018, Carroll et al 2019, Teale et al 2020. Observations of young children reveal much time and effort spent with voluntary skills practice when these skills interest children and form part of play or other authentic purposes -and this includes children from poor communities (Sibanda andKajee 2019, Bloch andMbolekwa 2021).…”
Section: Discussionmentioning
confidence: 99%
“…People go through a process of transition towards a larger life setting during childhood, from preschool to primary education [ 22 , 23 ]. Compared to the unorganized quality of preschool education, characterized by high parental involvement and less curricular input [ 24 ], children entering elementary school for systematic schooling undergo a shift in their life scenario, education methods, and the role of the primary instructor [ 23 , 25 ]. This will inevitably have various effects on the influence of the home environment on SFL.…”
Section: Introductionmentioning
confidence: 99%